Sri Lanka : Technical Assistance Report-Enhancing the Effectiveness of the Sri Lankan Securities Market Enforcement Program. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses the report of technical assistance mission to Sri Lanka. The report highlights that Sri Lanka has embarked on a program of reform intended to enable the country to emerge as an internationally competitive middle level economy. The mission concentrated on practical, operational steps that the Securities and Exchange Commission (SEC) could take to build capacity to increase the deterrent impact of its enforcement program in the current and anticipated regulatory environments. The mission recommended that the SEC continues to pursue measures to improve efficiency, effectiveness and accountability. In order to augment the impact of the enforcement program, the SEC is encouraged to foster public transparency to the extent possible without compromising confidential enforcement processes and activities. While the recommendations in this report will improve the effectiveness of the SEC's enforcement program, credible deterrence cannot be achieved without the new civil and administrative enforcement authority in the draft Securities Exchange Act.